(untitled) (International Journal of Engineering and Computer Science, 2013)
In this paper work have been suggested an effective way of tackling the gamut problem during the processing itself. It is not necessary to bring back the R, G, and B values to its bounds after the processing. The proposed algorithm does not reduce the achieved intensity by the enhancement process. The enhancement procedure suggested here is hue preserving. It generalizes the existing gray scale image enhancement techniques to color images. The processing has been done in RGB space itself and the saturation and hue values of pixels are not needed for the processing. The objective of contrast enhancement is to increase the visibility of details that may be obscured by deficient global and local lightness. The goal of color enhancement can be either to increase the colorfulness, or to increase the saturation. This method is also likely to avoid out-of-gamut or unrealizable colors.